A retrospective clinical case note review of 639 patients on clozapine and the management of clozapine-induced sialorrhoea (CIS). (1st September 2018) - Engelbrecht, Kristina; Miller, Helen; Mirfin, David
Background: Sialorrhoea is a common side-effect of clozapine, particularly nocturnally. There is limited evidence on prescribing, due to the limitations of the data currently available. Clinicians require clarity in order to optimise patient management, while avoiding further pharmacological side-effects. Aims: To collect information from clinical practice to establish: (1) the relationship between clozapine dose and clozapine-induced sialorrhoea (CIS); (2) treatment options utilised locally for the management of CIS; and (3) the effectiveness of such treatments, with emphasis on the time to symptomatic improvement and tolerability. Method: Retrospective clinical case note review of 639 patients on clozapine within the remit of a South London Mental Health Trust. Qualitative data was analysed using SPSS: Chi-square and unpaired t-tests where appropriate. Results: CIS manifests in 50% of patients and is significantly related to ethnicity. Greatest prevalence was noted from 300–500 mg, but there was no significant difference in dose between those with CIS and those without. 50% of patients develop CIS within the 21 days of starting clozapine, predominantly nocturnally. Oral hyoscine hydrobromide was primarily utilised, but with slow symptomatic improvement. Alternative treatments demonstrated superior effectiveness, including oxybutynin, amisulpride and atropine 1% eye drops. Response to treatment was fastest in pirenzipine, transdermal hyoscine and procyclidine. All treatments were well tolerated. Conclusions: Clinicians should be aware of the variety of potential methods to treat CIS. Management should be tailored on an individual basis, with consideration of the risks, benefits and patient preference.